The Mummy against the elements and other adventures - Universal Studios (Quezon City Unversal Studios, 2004)
Following a clue the discovered in the diaries of Alexander the Great, The O'Connel family return to ancient Egypt in pursuit of the scrolls of thebes. however - evil awaits them. imhotep uses all of his terrible powers to stop our heroes recovering the scrolls.
CD 1 (44 minutes and 24 seconds) -- CD 2. (40 minutes and 24 seconds)
VCD
Distributed in the Philippines by: MagnaVision.
Keywords: Mummy films